1994
DOI: 10.2466/pr0.1994.74.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Driving Anger Scale

Abstract: A cluster analysis of responses from more than 1500 college students to 53 potentially angering driving-related situations yielded a 33-item driving anger scale (alpha reliability = .90) with six reliable subscales involving hostile gestures, illegal driving, police presence, slow driving, discourtesy, and traffic obstructions. Subscales all correlated positively, suggesting a general dimension of driving anger as well as anger related to specific driving-related situations. Men were more angered by police pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
316
5
22

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 548 publications
(386 citation statements)
references
References 4 publications
10
316
5
22
Order By: Relevance
“…This need for further study is echoed by the fact that the higher levels of anger found for females were not consistent across all factors or measures of anger used by researchers (e.g., Deffenbacher, Oetting, & Lynch, 1994;Lajunen, Parker, & Stradling, 1998;Parker, Lajunen, & Summala, 2002;Sullman et al, 2006). Therefore, gender differences in emotionality while driving should continue to be a focus of research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This need for further study is echoed by the fact that the higher levels of anger found for females were not consistent across all factors or measures of anger used by researchers (e.g., Deffenbacher, Oetting, & Lynch, 1994;Lajunen, Parker, & Stradling, 1998;Parker, Lajunen, & Summala, 2002;Sullman et al, 2006). Therefore, gender differences in emotionality while driving should continue to be a focus of research.…”
Section: Discussionmentioning
confidence: 99%
“…Sound measures of dangerous driving are needed to understand differences and commonalties between aggression, negative cognitive/emotional driving, and risky driving. The Dula Dangerous Driving Index (DDDI) is one of several published measures and others include the Driving Anger Expression Inventory (DAX, Deffenbacher, Lynch, Oetting, & Swaim, 2002), the Driving Anger Scale (Deffenbacher, Oetting, & Lynch, 1994), the Driver's Angry Thoughts Questionnaire (DATQ, Deffenbacher, Petrilli, Lynch, Oetting, & Swaim, 2003), and the Propensity for Angry Driving Scale (PADS, DePasquale, Geller, Clarke, & Littleton, 2001). These latter surveys focus on measurement of anger.…”
mentioning
confidence: 99%
“…Furthermore, the propensity to become aggressive or angry while driving and may be analyzed especially when individuals with and without this trait are compared. 3,4 Deffenbacher et al 5 …”
Section: Resultsmentioning
confidence: 99%
“…Some authors 1,5,7 have found that individuals differ in their tendencies to become angry or aggressive when provoked or when feeling frustrated while driving. This finding suggests that anger may be a personality trait that leads to greater intolerance to certain situations, thereby causing aggressive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas there are measures of how stress is experienced in general (e.g., Sarason, Johnson, & Siegel, 1978) and in driving a car (e.g., Deffenbacher, Oetting, & Lynch, 1994) as well as measures of the related problem of flying phobia (e.g., Van Gerwen, Spinhoven, Van Dyck, & Diekstra, 1999), there are no known measures of air travel stress. This article describes the development and evaluation of a measure of air travel stress, the Air Travel Stress Scale (ATSS).…”
mentioning
confidence: 99%